Grammaticalisation paths of the Proto-Indo-European anaphoric pronoun *tód across the Germanic languages - Resmini, Cristina (Annali del Dipartimento di Studi Letterari, Linguistici e Comparati. Sezione linguistica, 2024)
Based on the accepted etymology and within a grammaticalisation framework, the Germanic reflexes of the Proto-Indo-European anaphoric pronoun *tód are believed to have diachronically acquired the functions of demonstrative pronoun, determiner, relative pronoun, argumental complementiser, and consecutive conjunction. According to the empirical data gathered from an extensive Early Germanic linguistic corpus created specifically for this study and considering cross-linguistic evidence especially from Latin, this paper suggests that the Germanic reflexes of *tód – which initially functioned as demonstrative pronouns – became determiners when followed by a noun and were directly reanalysed into argumental complementisers through a dipthyque inverse construction. In turn, the argumental complementiser was then reanalysed by extension into a consecutive conjunction in consecutive contexts, and into a relative d-Pronomen in the presence of an antecedent.